A REVIEW ON INTERPERSONAL FORGIVENESS - Isil Coklar; Ali Donmez (Nesne Psikoloji Dergisi, 2014)
Allthough almost everyone has some covert notions about it, attraction of forgiveness as an academic issue was limited with theology and philosophy for many years. In recent years social psychologists and clinical psychologists started to show interest both in self forgiveness and forgiving others. The purpose of this article is to review the definitions and models of forgiveness and giving information about the empirical research findings in Turkey.